Eating habits in mexican schooled children - Pérez Pedraza, Bárbara de los Ángeles; Monroy Velasco, Iris Rubi; Lara Acosta, Elda Madaí (Gaceta Médica de Caracas, 2021)
In Mexico, 35.5 % of school-age children are overweight or obese, the main cause of this excess is related to eating habits. A multivariate study was carried out to predict the eating habits of school children in function of social eating norms and perceived food advertising. Through random sampling, 132 girls and boys from upper primary were selected, to whom a questionnaire was applied to measure eating habits, food social norms, and perceived food advertising. En México, el 35,5 % de los niños en edad escolartienen sobrepeso u obesidad, la principal causa deeste exceso ponderal está relacionada con los hábitos alimentarios.